Hyperflexing the horse’s neck: a systematic review and meta-analysis - Uta König von Borstel; Kathrin Kienapfel; Andrew McLean; Cristina Wilkins; Paul McGreevy (Scientific Reports)
Abstract The article reports a meta-analysis of 58 peer-reviewed studies investigating on dorsoventral hyperflexion of the neck in horses, a practice under substantial public and scientific scrutiny for the past two decades. The following databases were last searched on 28.05.2023: CAB, Google Scholar, Web of Science, NAL/Agricola, PubMed and ScienceDirect. After evaluating the conclusions of each study, we performed statistical analyses to establish a consensus on welfare and performance (performance marks, kinematics and musculoskeletal) outcomes in horses performing with a hyperflexed head and neck posture (HNP). The analysis revealed that a significant majority of the articles (75% of n = 36; Z = 3.00; P>|Z|=0.0027) expressed concerns about the welfare of horses working in this posture. Parameters such as dressage training level, prior experience, duration, and method of achieving the hyperflexed posture did not influence welfare concern conclusions significantly (P > 0.1). Therefore, it appears that the practice impairs welfare regardless of how it is imposed. A concurrent assessment of the weight of evidence for performance benefits showed inconclusive results: approximately one-quarter of the studies showed benefits and one-quarter detrimental effects, while the largest proportion (44%) showed no significant effect on performance. On balance, it appears that the costs associated with hyperflexed HNPs exceed potential benefits.